SIGNAL TONOISERATIOOFIRSEEKER WITHANEWOPTICALFRACTAL MODULATOR - MOHAMMED, ABDULRAZAKA.S.; HAMEED, SAFAAMUSTAFA; MOHAMMED, ADlLH. (International Journal of Psychosocial Rehabilitation, 2020)
The signal-to-noise-ratio (SNR, S/N) is a technical term used to characterize the quality of the signal detection of a measuring system It is an important factor to check the quality of control system, Present work contains evaluate the S/N for the seeker with a new modulator that design by fractal function for IR band, and the results compared with the same seeker with a normal modulator. The advantage of this research that the modulator is a new design using a fractal function. This research describes the algorithms of Signal to Noise Ratio for the infrared seeker with Optical Fractal modulator compared with the seeker which has a normal modulator; the results were discussed and analyzed to design an optical modulator; which consists of two pattern circles. In our case, the standard well known as (S/NR) definition denoted as the global Signal for Noise Ratio of as (GS/NR). The OTF (Optical transfer function) and MTF (Modulation Transfer Function) has been calculated to find the ability to transmit the optical signal. The present technique compared with the technique used with a system using a CCD camera image sensor [13]